Analysis Moral Message Reflected in Leo Tolstoy’s Novel, War and Peace - Martina Girsang; Grace Widya Hutagalung; Nicha Sinaga; Anita Maharani Aritonang (Yayasan Karinosseff Muda Indonesia, 2023)
This study focuses on issues that arise while analyzing moral principles from a practical standpoint. The results of a study approach with the presentation of descriptive data analysis in Leo Tolstoy's work War and Peace were used to analyze the data. Reading, making notes, and analyzing quotes, words, remarks, and behaviors linked to the study's problem were the methods used to gather data. The study's findings demonstrate how the moral lesson is reflected in the war and peace fiction. en